2012
DOI: 10.1016/j.jvs.2011.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of direct and indirect endovascular revascularization based on the angiosome concept in patients with critical limb ischemia presenting with isolated below-the-knee lesions

Abstract: Achieving direct flow by angioplasty based on the angiosome concept in CLI patients with isolated BTK lesions is clinically important for AFS and freedom from MA and MALE. Limb salvage factors appear to differ between patients with and without direct flow from the feeding artery after EVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
115
2
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(125 citation statements)
references
References 20 publications
1
115
2
7
Order By: Relevance
“…As a result of an unclear distribution of the borderlines between angiosome, due to the existence of more than one scheme, we decided to adopt the general scheme of angiosome distribution, in which borderlines between angiosome match those outlined in the recent publication, "Long-term results of direct and indirect endovascular revascularization based on the angiosome concept in patients with critical limb ischemia presenting with isolated below-the-knee lesions "by Osamu Iida et al 4 Schematic diagram is shown in (Figure 1). …”
Section: Methods Of Data Collectionmentioning
confidence: 99%
“…As a result of an unclear distribution of the borderlines between angiosome, due to the existence of more than one scheme, we decided to adopt the general scheme of angiosome distribution, in which borderlines between angiosome match those outlined in the recent publication, "Long-term results of direct and indirect endovascular revascularization based on the angiosome concept in patients with critical limb ischemia presenting with isolated below-the-knee lesions "by Osamu Iida et al 4 Schematic diagram is shown in (Figure 1). …”
Section: Methods Of Data Collectionmentioning
confidence: 99%
“…Számos tanulmány igazolta az endovascularis kezelés végtagmentő hatását, és a legnagyobb előnye ennek a technikának a minimálisan invazív jelleg, a kevesebb in tézeti tartózkodás és az alacsonyabb mortalitás, illetve morbiditás [4][5][6][7][8][9][10][11][12]. Tekintetbe véve azt, hogy az inter venció elsődleges célja az amputáció megelőzése és a funkcionális végtag megmentése, a térd alatti PTA elsőd legesen ebből a célból történik.…”
Section: Angioplasticaunclassified
“…Tekintetbe véve azt, hogy az inter venció elsődleges célja az amputáció megelőzése és a funkcionális végtag megmentése, a térd alatti PTA elsőd legesen ebből a célból történik. Nagy nemzetközi vizs gálatok adatai szerint jelenleg a térd alatti PTAval 56-81%ban lehet végtagmentést elérni [3][4][5][6][7][8]. Számos tanulmány szerint az angioplastica sikere javította a vég tagmentést, de a hosszú távú eredményekről csak kevés tanulmány készült [11][12][13].…”
Section: Angioplasticaunclassified
See 1 more Smart Citation
“…Consequently, the size, location, and extent of the necrosis may impact the necessity for multi-vessel revascularization. Furthermore, revascularization of the angiosome (a three-dimensional vascular territory supplied by specific source artery), has been shown to improve healing rates, using either endovascular or surgical therapies, when compared to revascularization of the non-angiosome territory [11][12][13]. However, realistically the angiosomebased revascularization strategy may be limited by the length and/or complexity of disease, the extent of collateralization, and the anatomic variability among patients, including anatomic anomalies [5].…”
Section: Anatomic Considerationsmentioning
confidence: 99%